Adaptive evolution of Saccharomyces cerevisiae and its application in co-culture with Saccharomyces kudriavzevii in the production of fermented Myrciaria jaboticaba (Research, Society and Development, 2021)
The objective of this work was to apply the adaptive evolution technique using the Saccharomyces cerevisiae T73 strain to increase its tolerance to ethanol and to evaluate its behavior in co-culture with Saccharomyces kudriavzevii CR85 in the production of fermented Myrciaria jaboticaba. Fermentations were carried out at 25 °C for 186 hours under agitation of 150 rpm, according to a central. The consumption of sugar, ethanol, glycerol and acetic acid formed during the fermentation process was evaluated. The results showed that there is an improvement in ethanol tolerance in S. cerevisiae T73 when submitted to the evolution process. Its use for the production of fermentation of Myrciaria jaboticaba in co-culture shows that the highest yield was observed when 0.0372 g.L-1 and 0.0648 g.L-1 of S. cerevisiae T73 PE (that underwent evolution) and CR85 respectively. These results differed statistically from the experiments using the original T73 strain. Regarding the production of ethanol in co-culture there is a significant increase when using the evolved T73 strain, showing possible changes in the primary metabolism of the ethanol production process, due to the changes promoted during the adaptive evolution of the T73 strain. The results show the potential of the new strain for the production of fermented with higher concentrations of sugars in the must.